Measuring the Impact of Learning Evaluation on the Readiness of Nursing Graduates in the World of Work - Hardjito S. Darmojo; Al-bahra Al-Bahra; Fathiyati Fathiyati (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2026)
Introduction: The transition from nursing education to professional practice remains a critical challenge, often characterized by a gap between academic assessment systems and real-world clinical demands. Learning evaluation plays a pivotal role not only in measuring academic achievement but also in shaping graduate nurses’ work readiness. However, the extent to which different components of learning evaluation contribute to work readiness remains underexplored. Objective: This study aimed to analyze the impact of learning evaluation on the work readiness of nursing graduates entering the healthcare workforce. Methods: A quantitative cross-sectional correlational design was employed. A total of 236 nursing graduates from diploma and bachelor programs were selected using stratified random sampling. Data were collected using validated questionnaires measuring learning evaluation components (formative assessment, summative assessment, clinical simulation, and preceptor feedback) and the Work Readiness Scale for Graduate Nurses (WRS-GN). Data were analyzed using Pearson correlation and multiple linear regression analysis with a significance level of p < 0.05. Results: Learning evaluation demonstrated a significant relationship with work readiness (r = 0.658, p < 0.001). Multiple regression analysis revealed that learning evaluation explained 56.9% of the variance in work readiness (R² = 0.569). Among the components, preceptor feedback emerged as the most dominant predictor (β = 0.356, p < 0.001), followed by clinical simulation (β = 0.267, p < 0.001) and formative assessment (β = 0.184, p = 0.006). Summative assessment showed no significant effect on work readiness (p = 0.135). Conclusion: Learning evaluation significantly influences nursing graduates’ work readiness, with practice-based evaluation components such as preceptor feedback and clinical simulation playing the most critical roles. The findings highlight the need to shift from traditional summative-based evaluation toward competency-based and clinically integrated assessment systems to better prepare nursing graduates for real-world healthcare demands